Arsenic sorption on zero-valent iron-biochar complexes - Bakshi, Santanu; Banik, Chumki; Rathke, Samuel J.; Laird, David A. (Water research (Oxford), 2018)
Arsenic (As) is toxic to human and is often found in drinking water in India and Bangladesh, due to the natural abundance of arsenides ores. Different removal procedures such as precipitation, sorption, ion exchange and membrane separation have been employed for removal of As from contaminated drinking water (CDW), however, there is a critical need for low-cost economically viable biochar modification methods which can enhance As sorption. Here we studied the effectiveness of zero-valent iron (ZVI)-biochar complexes produced by high temperature pyrolysis of biomass and magnetite for removing As5+ from CDW. Batch equilibration and column leaching studies show that ZVI-biochar complexes are effective for removing As5+ from CDW for the studied pH range (pH ∼7–7.5) and in the presence of competing ions. XPS As 3d analysis of ZVI-biochar complexes exposed to As5+ in the batch and column studies show primarily As3+, indicating simultaneous oxidation of Fe° to Fe3+ and reduction of As5+ to As3+. SEM-EDS and XRD analyses show isomorphous substitution of As3+ for Fe3+ in neo-formed α/γ-FeOOH on biochar surfaces, which is attribute to co-precipitation. This study also demonstrates the efficacy of pyrolyzing biomass with low-cost iron ores at 900 °C to rapidly produce ZVI-biochar complexes, which have potential to be used for treatment of As CDW. [Display omitted] •Zero-valent iron (ZVI) biochar complexes are effective for As5+ removal from water.•Co-pyrolysis of low cost iron ore and biomass can produce ZVI biochar complexes.•Simultaneous oxidation of Fe° to Fe3+ and reduction of As5+ to As3+ occurred.•As3+ sorption attributed to isomorphous substitution of As3+ for Fe3+ in α/γ-FeOOH.•ZVI-biochar complex developed in this study can mitigate As contamination risk.